PERILAKU MEKANIK TARIK BAMBU DAN POTENSI APLIKASINYA SEBAGAI PERKUATAN TANAH PADA TIMBUNAN - Suwartanti, Suwartanti (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT The main obstacle in building a construction in soft soil is the big settlement which occurs in such soil. One of the techniques to solve this problem is to hamper geosynthetics on this soft soil and create a compacted embankment from good soil above the soft soil. The application of this technique is quite effective, but due to economic problem and environmental awareness, the use of another material which is cheaper and comes from nature is in urgent need. In the past our ancestors have used bamboo as soil reinforcement. Unfortunately the publications and researches concerning this matter are still very few. This study is aimed to investigate the tensile strength of woven bamboo and its potential application for soil reinforcement in an embankment. Three variants of bamboos are used in the experiment. The samples are taken from the outer parts (skin) and inner parts, with and without nodes. The shape and dimension of the samples are designed to represent the actual shape and dimension of woven bamboo. From the experiment, the maximum tensile strength obtained from tensile strength and strain analysis is 395.533 kN/m’. The outer part of bamboo is categorized as brittle material while the inner part is ductile. Based on these findings and considering bamboo’s rough surface and its lifetime, bamboo is potential for soil reinforcement in an embankment to replace a particular function of geosynthetics. Keywords: bamboo, soil reinforcement, embankment